THE FINANCIAL CRISIS AND COVID-19 PANDEMIC IN SOUTH ASIA: POVERTY ALLEVIATION POLICY FROM ISLAMIC PERSPECTIVE TO ACHIEVE SUSTAINABLE DEVELOPMENT - Hossain, Muhammad Mostofa; Haji Abdullah , Luqman; Rosele, Muhammad Ikhlas (Online Journal of Islamic Management and Finance (OJIMF), 2021)
Nearly 700 million people of the world’s population subsist under ruthless poverty that causes significant struggle in attaining basic needs. A well-built financial strength, fair distribution and growth of wealth are indispensable to nullify those obstacles. Sustainable development is the fundamental trail for socio-economic steadiness. The COVID-19 outbreak has adversely affected global financial growth and placed a rigorous challenge to achieve sustainable development sticking multiple jeopardizes with the possible high unemployment rate and the poverty line bulge. Maslaha being the core concept of Islam protects wealth as of necessity to alleviate poverty and helical financial growth in people’s lives that authenticate sustainable progress. Islam hence advocates a bunch of profound alternatives to exile poverty and ensure sustainable development. The article aims to propose policies through the installation of Islamic financial tools to get rid of the poverty caused by the COVID-19 financial crisis in South Asia. Hence, the expected findings from the article would be the Islamic mechanisms of COVID-19 poverty eradication which are sustainable and value-structured.